OC-020 Is Taking Histological Biopsies in Patients With Gastritis A Waste of Time and Money?. (17th August 2016) - Dawson, L; Baker, J; Ala, K; Shutt, J; Jupp, J; Bridger, S
Abstract : Introduction: The clinical usefulness of taking gastric biopsies in patients with endoscopic gastritis is unclear. There are international recommendations in support of this but the cost effectiveness is questionable and there is little evidence that biopsies influence patient management. 1 Methods: In 2014, 1109 patients were identified as having endoscopic gastritis based on a retrospective review of the hospital's Endoscopy database. Of these patients, 610 had a urease test, 90 had both urease testing and gastric histology, 378 just had histology and 31 had neither test. A more detailed review of the patient's clinical notes and histology was undertaken for 114 consecutive gastritis patients who had gastric biopsies sent for histological analysis over a 3 month period (Aug-Oct). Results: 56% of the patients were female (64/114) with an average age of 65 years (range 17–91). 76% of these patients were taking a PPI at the time of endoscopy. Dyspepsia/reflux (43%) was the commonest primary indication, followed by anaemia/GI bleeding (24.5%), dysphagia (10.5%), nausea/vomiting (6%) and miscellaneous others. 88.5% of patients had at least 2 antral biopsies taken. 17.5% of patients had both antral and corpus biopsies. 6% of patients had both urease testing and histology. No serious pathology was found on any of the histological samples. The commonest histological diagnosis was chemical, reactive or inflammatory gastritis (70%), followed by normal (17%), Helicobacter pylori (Hp) gastritis (10.5%), intestinal metaplasia (1%) and fundic gland polyp (1%). Conclusion: Despite recommendations to the contrary, 1 we found 42% of patients with uncomplicated gastritis still have gastric biopsies sent for histopathological analysis. The reasons why an Endoscopist chooses to request histology rather than a urease test are not clear. We suspect decision-making is influenced by whether the patient is taking a PPI with a perception that this may reduce the sensitivity of urease testing. However the manufacturer of Endosc-Hp™ reports a sensitivity of 94.4% in detecting Hp even if the patient is taking a PPI (email comm). Consequently there would seem to be no additional value in sending histology in this group of patients. The cost savings are considerable. Even in a DGH serving a population of 220, 000, the annual cost savings of carrying out urease testing rather than histology in patients with uncomplicated gastritis would amount to at least £37000. This study supports the Royal College of Pathologists contention that "biopsy for histological classification of gastritis is unlikely to change management" and taking biopsies for patients with uncomplicated gastritis "is not recommended." 1 Reference: 1 Loughrey MB, Johnston BT. Frontline Gastroenterology 2014;5 :88–95. Disclosure of Interest: None Declared